Baricitinib treatment for refractory skin changes in POEMS syndrome: a case report - Xie, Jingjing; Li, Zhiling; Jiang, Yubao; Tang, Dabin; Qiu, Xia; Jia, Ertao; Zhang, Jianyong (Frontiers in Pharmacology, 2023)
Polyneuropathy, organomegaly, endocrinopathy, monoclonal plasma cell disorder, and skin changes (POEMS) syndrome is a multisystem disorder that has limited treatment options. Here, we described a case of a 55-year-old female subject who was treated for multiple drugs, but the skin symptoms continued to progress; the patient responded well to baricitinib. This suggests that JAK/STAT signaling pathways play an essential role in the pathological process of POEMS syndrome.